1992
DOI: 10.1159/000282323
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Benign Hyperplastic Prostate Tissue into Nude Mice: First Results of Systemic Therapy

Abstract: Xenografts of human benign hyperplastic prostate tissue (BPH) have been established as a model for the investigation of the etiology of BPH. In this paper it is our aim to answer the question of whether this model is useful for the established therapy of the disease. Additionally we try to evaluate the value of a commonly used plant extract for the therapy of BPH. Is there any influence of the extract from Sabal serrulatum on the BPH tissue in our model? Human BPH tissue from 2 patients was transplanted into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…41 Cells derived from human tissue culture and primary surgical specimens were transplanted into athymic rats or mice. Transplants displayed histologically typical BPH acini and stroma.…”
Section: Xenograft Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Cells derived from human tissue culture and primary surgical specimens were transplanted into athymic rats or mice. Transplants displayed histologically typical BPH acini and stroma.…”
Section: Xenograft Modelsmentioning
confidence: 99%
“…Equivocal data have been reported on the effect of dihydrotestosterone on the growth of tissue implants. 38,41,42 Transgenic mice Transgenic mice are used as a model to study the consequence of various transforming events on the prostate gland. Several prostate-speci®c regulatory elements have been evaluated for their ability to direct heterologous gene expression speci®cally and reproducibly to the prostate in transgenic mice.…”
Section: Xenograft Modelsmentioning
confidence: 99%
“…Preliminary studies on human BPH tissue xenografts in nude mice have indicated that successful preservation of tissue morphology is possible for up to 8 weeks [8][9][10]. However, this is not long enough for proliferation of prostate tissue in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In an alternative in vivo system (human prostatic tissue transplanted to the nude mouse) the synergistic effects of DHT and estrogen were observed, as well as sabalextract-induced inhibition or slowing of prostatic hyperplasia (34). Other animal experiments confirmed the antiandrogenic effects of lipophilic saw palmetto extracts (26).…”
Section: Serenoae Repentis Fructusmentioning
confidence: 88%